2022
DOI: 10.3389/fnut.2022.843808
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Hydrodynamic Cavitation: A Novel Non-Thermal Liquid Food Processing Technology

Abstract: Hydrodynamic cavitation (HC), as a novel non-thermal processing technology, has recently shown unique effects on the properties of various liquid foods. The extreme conditions of pressure at ~500 bar, local hotspots with ~5,000 K, and oxidation created by HC can help obtain characteristic products with high quality and special taste. Moreover, compared with other emerging non-thermal approaches, the feature of the HC phenomenon and its generation mechanism helps determine that HC is more suitable for industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…HC phenomenon, discovered by Euler [5] in water wheels as early as in 1756, is a rapid phase-change phenomenon, including formation, growth, and collapse, triggered by local pressure change [6] , [7] , and releases tremendous energy into surrounding liquids, creating unique reaction environment with local high pressures and temperatures and strong oxidation/reduction effects [8] , [9] , [10] . The sonochemical effect induced by HC has been widely investigated and applied in various chemical and environmental applications in the past 30 years: degradation of organic matter [11] , disinfection [12] , disintegration of waste activated sludge [13] , emulsification (including biodiesel synthesis) [14] , delignification [15] , food processing [16] , flotation [17] , surface finishing and washing [18] , denitration [19] , heat generation [20] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…HC phenomenon, discovered by Euler [5] in water wheels as early as in 1756, is a rapid phase-change phenomenon, including formation, growth, and collapse, triggered by local pressure change [6] , [7] , and releases tremendous energy into surrounding liquids, creating unique reaction environment with local high pressures and temperatures and strong oxidation/reduction effects [8] , [9] , [10] . The sonochemical effect induced by HC has been widely investigated and applied in various chemical and environmental applications in the past 30 years: degradation of organic matter [11] , disinfection [12] , disintegration of waste activated sludge [13] , emulsification (including biodiesel synthesis) [14] , delignification [15] , food processing [16] , flotation [17] , surface finishing and washing [18] , denitration [19] , heat generation [20] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…
Fig. 6 Life cycle of a cavitation bubble (A), conventional non-rotational hydrodynamic cavitation reactor (NRHCRs) (B), and representative advanced rotational HCRs (ARHCRs) (C) [118] .
…”
Section: Hcrs: Mechanism and Performancementioning
confidence: 99%
“… [39] , [40] . Since Pandit and Joshi [41] first applied HC to oil hydrolysis in 1993, HC has demonstrated great commercialization prospects in various applications, e.g., water treatment [42] , [43] , emulsification [44] , delignification [45] , food processing [46] , [47] , flotation [48] , surface finishing [49] , heat generation [50] , nanomaterial synthesis [51] , and even graphene exfoliation [52 . Numerous studies have demonstrated that HC can efficiently induce a sonochemical effect similar to ultrasound, with high scalability and low cost [53] , [54] .…”
Section: Introductionmentioning
confidence: 99%